Home » Make (frac{a}{x}) the subject of formula (frac{x + 1}{x – a}) = m

Make (frac{a}{x}) the subject of formula (frac{x + 1}{x – a}) = m

Make (frac{a}{x}) the subject of formula (frac{x + 1}{x – a}) = m

  • A.
    (frac{m – 1}{m + 1})
  • B.
    (frac{m + 1}{1 – m})
  • C.
    (frac{m – 1}{1 + m})
  • D.
    (frac{m + 1}{m – 1})
Correct Answer: Option A
Explanation

(frac{x + a}{x – a}) = m
x + a = mx – ma
a + ma = mx – x
a(m + 1) = x(m – 1)
(frac{a}{x}) = (frac{m – 1}{m + 1})

Related:  If P varies inversely as the square root of q, where p = 3 and...